Differential Risks for Adverse Outcomes 3-Years after Kidney Transplantation Based on Initial Immunosuppression Regimen: A National Study - Dharnidharka, Vikas R (Transpl Int, 2016)
We examined integrated national transplant registry, pharmacy fill and medical claims data for Medicare-insured kidney transplant recipients in 2000–2011 (n=45,164) from the United States Renal Data System to assess efficacy and safety endpoints associated with 7 early (first 90 days) immunosuppression (ISx) regimens. Risks of clinical complications over 3 years according to IS regimens were assessed with multivariate regression, including adjustment for covariates and propensity for receipt of a non-reference ISx regimen. Compared to the reference ISx (thymoglobulin induction with tacrolimus, mycophenolate and prednisone maintenance), sirolimus-based ISx was associated with significantly higher 3-year risks of pneumonia (adjusted hazard ratio, aHR 1.45;P<0.0001), sepsis (aHR 1.40;P<0.0001), diabetes (aHR 1.21;P<0.0001), acute rejection (AR; adjusted odds ratio, aOR 1.33;p<0.0001), graft failure (aHR 1.78;p<0.0001), and patient death (aHR 1.40;P<0.0001), but reduced skin cancer risk (aHR 0.71;p<0.001). Cyclosporine-based IS was associated with increased risks of pneumonia (aHR 1.17;p<0.001), sepsis (aHR 1.16;p<0.001), AR (aOR 1.43;p<0.001) and graft failure (aHR 1.39p<0.001), but less diabetes (aHR 0.83;p<0.001). Steroid-free ISx was associated with reduced risk of pneumonia (aHR 0.89;p=0.002), sepsis (aHR 0.80;p<0.001) and diabetes (aHR 0.77;p<0.001) but higher graft failure (aHR 1.35;p<0.001). Impacts of ISx over time warrant further study to better guide ISx tailoring to balance efficacy and morbidity.